Bacterium consortium drives compost stability and degradation of organic contaminants in in-vessel composting process of the mechanically separated organic fraction of municipal solid waste (MS-OFMSW). (February 2021) - Graça, Jessica; Murphy, Brian; Pentlavalli, Prasanna; Allen, Christopher C.R.; Bird, Eoin; Gaffney, Michael; Duggan, Tim; Kelleher, Brian
Abstract: Commercial composting of the mechanically separated organic fraction of municipal solid waste (MS-OFMSW) is employed to stabilize municipal organic waste. Its feasibility is linked to process efficacy and compost stability. Threshold values for stability are imposed by regulatory frameworks. Limited reuse options exist for this material often due to the presence of organic pollutants. The optimisation of the composting process is required to reach stability in a viable timeframe. We evaluated the effects on compost stability and the degradation of organic contaminates by using wood shavings as a bulking agent and increasing the turning frequency in a pilot scale process. The use of wood shavings decreased the time required for compost stability while turning frequency had no impact. The addition of wood shavings to the initial feedstock stimulated microbial activity that in turn decreased the time to compost stability and enhanced the degradation of detected PAHs and short-chain phthalates. Graphical abstract: Unlabelled Image Highlights: Wood shavings used as bulking agent increased the composting efficiency and stability. Increased turning frequency of the material does not impacted compost stability. PAHs and phthalates concentrations decreased after the composting process. Composting has potential to remediate organic contaminates from MS-OFMSW.